Emerging philosophies for educational programmes and adult learning in Nigeria (2024)
There are principles from pragmatism, existentialism, humanism, and radicalism that have relevance for educational practices in Nigeria, notwithstanding the ongoing debate in educational discussions over whether Nigerian education is based on any philosophy. Traces of these philosophies can be read in educational thoughts, trends and practices in Nigeria. The fact that Nigeria had for years engaged in varied educational activities presupposes that if there is not a single philosophy, then there are many philosophies guiding the country's educational practices. From the colonial era to the contemporary society, educational practices have changed because of the educational objectives that Were set in responding to the changing society. From these changes, one can show that there are orientations behind the educational practices in Nigeria. Earlier explanations discussed these ideas as separated and unrelated but this paper uses narrative review to respond to the question: what are the emerging philosophies for educational programmes in Nigeria. This was done by providing a general overview and interpretations of educational thoughts and activities. It considers those elements of many philosophies of education that have guided activities especially in educational activities generally, and adult education particularly while it teased out the common elements in the system. The four philosophies place emphasis on individuality awareness creation and functionality of learners in organisations and community they find themselves.